Scientific integrity and anti-doping regulation. Issue 2 (3rd April 2019) - Pielke, Roger; Boye, Erik
ABSTRACT: The paper addresses a fundamental challenge facing anti-doping regulation in sport: securing scientific integrity. The importance of evidence in anti-doping is similar to that found across many fields where science and expertise meet policy, ethics and regulation. We argue that a growing body of evidence indicates that anti-doping regulation under the World Anti-Doping Agency is sometimes arbitrary and too often not grounded in a solid foundation of evidence. We document shortfalls in standards of scientific integrity in four contexts: (1) the prevalence of doping, (2) performance benefits and health risks, (3) errors and inconsistencies in accusation, and (4) the evaluation of anti-doping policies. We give several suggestions to enhance scientific integrity in anti-doping regulation and argue that greater transparency will help to reduce inconsistencies and errors.